Research capability of Filipino teacher educators: insights from a criterion-referenced test - Amanonce, Jay-cen T.; Temporal, Conchita M.; Vecaldo, Rudolf T.; Calubaquib, Jhoanna B.; Tamayao, Antonio I.; Malana, Maribel F.; Tamayo, Ria A.; Calanoga, Marie Claudette M. (International Journal of Evaluation and Research in Education (IJERE), 2025)
The research capability of Filipino teacher educators has been found to be lacking, which limits their ability to contribute effectively to academic research. This study aims to assess their foundational knowledge in research, as understanding their capability is essential for improvement. A quantitative approach was employed, evaluating 100 teacher educators from a state university in Northern Philippines using the research capability test (RCT), a validated criterion-referenced tool. Results showed that teacher educators generally possess average research capability, with significant differences based on educational attainment, field of specialization, and research teaching experience. Those with doctoral degrees, specializations in natural sciences and mathematics, and experience teaching research demonstrate higher capability. These findings suggest that, while basic research knowledge exists, there is a critical need for focused professional development programs to address specific gaps. Strengthening research capability not only improves the teacher educators’ performance but also enhances the overall quality of research outputs in the Philippine education system, ensuring long-term academic growth and global competitiveness.